2017
DOI: 10.1177/1460458217738121
|View full text |Cite
|
Sign up to set email alerts
|

Who uses apps in health promotion? A target group analysis of leaders

Abstract: User characteristics should be considered when designing features for e-health or m-health applications, as the developed solution should aim to support this specific target group. This study explores the effect of user characteristics (personality, health state, stress/recovery state, leadership behavior) on the interest and likelihood of using an app for health promotion activities at the workplace. Leaders are a key factor for the success of workplace health promotion; therefore, the target group of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…Health-promoting leaders often use health apps and are positively related to health-related resources. For example, Bregenzer et al (2017) showed that such leaders use healthpromoting apps more often than non-health-promoting leaders, which suggests that health-promoting leaders are more aware of their health condition and more likely to communicate with others on health-related issues. Bregenzer et al (2019) also found that health-promoting leadership is positively related to healthrelated resources, such as task resources.…”
Section: Other Outcome Variablesmentioning
confidence: 99%
“…Health-promoting leaders often use health apps and are positively related to health-related resources. For example, Bregenzer et al (2017) showed that such leaders use healthpromoting apps more often than non-health-promoting leaders, which suggests that health-promoting leaders are more aware of their health condition and more likely to communicate with others on health-related issues. Bregenzer et al (2019) also found that health-promoting leadership is positively related to healthrelated resources, such as task resources.…”
Section: Other Outcome Variablesmentioning
confidence: 99%
“…By crafting a compelling health-related vision, health-promoting leaders clearly emphasize the importance of promoting health in the workplace and this leads to more awareness of health and thus contributes to an increase in employees' health resources (Bregenzer et al , 2019b). More precisely, we aim to investigate how leaders enhance employee health when they engage in health-promoting leadership and therefore motivate and encourage healthy employee behavior.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Smartphones allow continuous, non-intrusive monitoring of participants, reach more people, guarantee their anonymity, and tailor interventions based on individual characteristics and needs [6,7]. Mobile apps that monitor mental health have potential in managing burnout, stress, depression, and anxiety [8][9][10][11]. However, despite some promising results, there is little evidence on smartphone-based interventions [7].…”
Section: Introductionmentioning
confidence: 99%